2001
DOI: 10.1016/s0092-8674(01)00472-x
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Themes in Lipid Rafts and Caveolae

Abstract: vivo (Figure 1B). It has been proposed that caveolins participate in vesicular trafficking events and signal Biomedical Science Tower (BST), Room E1356 Pittsburgh, Pennsylvania 15261 transduction processes by acting as scaffolding proteins to organize and concentrate specific lipids (choles-2 Department of Molecular Pharmacology Division of Hormone-Dependent Tumor Biology at terol and glyco-sphingolipids) and lipid-modified signaling molecules (Src-like kinases, H-Ras, eNOS, and The Albert Einstein Comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
496
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 551 publications
(504 citation statements)
references
References 48 publications
3
496
0
Order By: Relevance
“…SFKs are thought to be localized predominantly at lipid rafts (29,44), and we found that the ganglioside GM1, a marker for lipid rafts (29,30), was also enriched and localized along the apical surface of crypt IECs. Lipid rafts may therefore recruit SFKs to the apical surface of crypt IECs.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…SFKs are thought to be localized predominantly at lipid rafts (29,44), and we found that the ganglioside GM1, a marker for lipid rafts (29,30), was also enriched and localized along the apical surface of crypt IECs. Lipid rafts may therefore recruit SFKs to the apical surface of crypt IECs.…”
Section: Discussionmentioning
confidence: 65%
“…S6A). Moreover, staining of the ganglioside GM1 as a marker for lipid rafts (29,30) with the B subunit of cholera toxin revealed a pattern similar to that apparent for the three SFKs in intestinal crypts (see Fig. S6B).…”
Section: Generation Of Iec-specific Csk Cko Micementioning
confidence: 59%
“…For endothelia of several organs of the body, experimental evidence points to the existence of what has been referred to as two sets of physiological pores: large pores responsible for the transport of proteins and small pores designed for the diffusion of small solutes. Opinions differ widely concerning which features of endothelial cells found in these organsfenestrae, the transtubulovesicular system including caveolae, and interendothelial clefts-are the morphological correlates to the two pore system suggested by the physiological data (Predescu et al, 1997;Michel and Curry, 1999;Silverstein, 1999;Smart et al, 1999;Galbiati et al, 2001;Bendayan, 2002;Feng et al, 2002;Simionescu et al, 2002).…”
Section: Biomolecular Size Exclusion Of Dextrans Equal To or Greater mentioning
confidence: 99%
“…Therefore, specific membrane compartments are required in order to concentrate and organize these signal molecules. These specific membrane compartments, also commonly referred to as the lipid rafts, are composed of cholesterol and glycolipids [1,2], and predominantly harbor a host of receptors and signaling molecules, allowing them to mediate a variety of cellular events, including cellular signaling, pathogenic invasion, immune responses, and cholesterol homeostasis [3][4][5][6]. Because the lipid rafts are loaded with many receptors for epidermal growth factor (EGF) [7], platelet-derived growth factor [8], nerve growth factor [9], insulin [10], insulin-like growth factor [11], transforming growth factor [12], and tumor necrosis factor [13], these rafts might act as platforms which initiate various cellular signal pathways.…”
Section: Introductionmentioning
confidence: 99%